Protein‐Directed Synthesis of Lead(II) and Temperature Dual‐Responsive Red Fluorescent Gold Nanoclusters and Their Applications in Cellular and Bacterial Imaging. Issue 5 (29th April 2016) - Kong , Lingcan; Ma, Guangyuan; Liu, Wenwei; Zhu, Pengfei; Xue, Qiang; Ling, Xia
Abstract: Abstract : Low toxicity and fluorescent nanomaterials have many advantages in biological imaging. Herein, we report a simple protein‐directed synthesis of water‐soluble and fluorescent gold nanoclusters (NCs) using bovine serum albumin (BSA) as the stabilizing agent. The as‐prepared Au NCs show red fluorescence with a maximum peak at about 630 nm (quantum yield 7.6 %) and are characterized in terms of photoluminescence spectrum, photoluminescence excitation spectrum, transmission electron microscopy, Fourier transform infrared spectroscopy (FT‐IR), circular dichroism spectra (CD) and X‐ray photoelectron spectroscopy. The resultant Au NCs are shown to be viable fluorescent probes for the determination of lead(II) ion and temperature due to aggregation‐induced quenching of fluorescence. Furthermore, the nanosensor exhibits high sensitivity to Pb 2+ ion with a detection limit of 7.9 nmol L –1 and has been demonstrated for determination of Pb 2+ ion in real water samples including tap water and mineral water. In addition, with the advantages including red fluorescence and good biocompatibility, the resultant BSA−Au NCs could be used as nanosensors for Pb 2+ ion and temperature in biological imaging. Abstract : A simple protein‐directed synthesis of water‐soluble and fluorescent gold nanoclusters (NCs) using bovine serum albumin (BSA) as the stabilizing agent is reported. The resultant Au NCs are shown to be viable fluorescent probes for the determination of lead(II) ion and temperature due to aggregation‐induced quenching of fluorescence. Moreover, lead(II) ion and temperature dual responsive Au NCs have been successfully applied to cellular and bacterial imaging.